2003
DOI: 10.1007/s00244-002-2028-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Metal Content of Some Benthic Species from Coastal Waters of the Florida Panhandle Using High-Resolution Inductively Coupled Plasma Mass Spectrometry (ICP-MS) Analysis

Abstract: Benthic marine invertebrates, sediment, and water from several locations along the Florida panhandle coast from St. Joseph Bay in the west to the mouth of the Wakulla River in the east, including from several river estuaries, were analyzed by double focusing ICP-MS (Finnigan MAT ELEMENT) for Cd, Hg, Pb, Cu, Zn, and As. All were detected in all samples. Sponges generally contained higher levels of Cd than other species. Microciona prolifera sponges from St. Joseph Bay had higher As levels (8.1-13.6 microg/g dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…The biological roles ascribed to Cu and its ability to adopt various redox states [39] may account for the high variation in its concentration between the species studied here. This ranged from 2.7 g/Kg for S. clavatus to 38.6 g/Kg for Haliclona sp.2, a range comparable to values recorded from species all over the world [9], [40], [17], [41].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The biological roles ascribed to Cu and its ability to adopt various redox states [39] may account for the high variation in its concentration between the species studied here. This ranged from 2.7 g/Kg for S. clavatus to 38.6 g/Kg for Haliclona sp.2, a range comparable to values recorded from species all over the world [9], [40], [17], [41].…”
Section: Discussionsupporting
confidence: 74%
“…In some cases a range of concentrations was published, but no statistical analysis was performed [6], [8], [9]. This is due to the relatively large effect of the trace metals content of sediment particles found inside sponges, causing the geological contribution to the measurement to mask the biological one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations measured were high compared with previously published ranges of element concentrations in other sponge species (Verdenal et al, 1985;Denton et al, 1999;Philp et al, 2003;Negri et al, 2006;Rao et al, 2009). Concentrations of these elements were also found to be substantially higher than for other sponges from Darwin Harbour (Paratetilla sp., Iotrochota sp.…”
Section: Discussionsupporting
confidence: 55%
“…Accordingly, sea urchins are considered to contribute significantly to the transfer of metals and other pollutants to higher trophic levels (Muir et al, 1999). The ascidians have been investigated for use in biomonitoring studies and have been shown to accumulate a range of metals such as vanadium (V), Cu, Pb and Zn (Denton, Concepcion, Wood, & Morrison, 2006;Philp, Leung, & Bradley, 2003). These tunicates have been used to compare availability of metals such as Cu and Pb in contaminated and natural harbours (De Caralt, López-Legentil, Tarjuelo, Uriz, Turon, 2002).…”
Section: Introductionmentioning
confidence: 99%